Implementation of government-directed policy in the hospital setting: a modified Delphi study - S. M. Havers; E. Martin; A. Wilson; L. Hall (BMC, 2019)
Abstract Background In the last 20 years governments have sought to introduce policy that improves the quality of care provided in hospitals, yet little research has been done to understand how these policies are implemented, factors that affect the implementation process or what should be considered by decision-makers during policy development or implementation planning. Experts with real-life experience in the introduction and implementation of policy are best placed to provide valuable insight into practical issues that affect implementation and the associated outcomes of these policies. Methods A modified Delphi study of experts in hospital policy development and implementation was undertaken to investigate factors influencing the implementation of government-directed policy in the hospital setting. This study built on the findings of two previous studies - a qualitative study of clinician perspectives of policy implementation and a systematic review and meta-synthesis, in which common contextual factors and policy characteristics associated with policy implementation were ascertained. International experts with extensive experience in government-directed policy implementation at global, national, corporate, jurisdictional and organisational levels were asked to provide opinions on predetermined factors and the feasibility of considering these in policy development and implementation planning. Survey design and analysis was guided by the Consolidated Framework for Implementation Research. Results Eleven experts from four countries and with different health system perspectives participated in the study. Consensus was reached on the importance of all predetermined factors in the first survey round with additional factors for investigation highlighted by participants for examination in subsequent rounds. On study completion, expert consensus was reached on 24 factors of importance; only 20 of these factors reached consensus for feasibility. Conclusions Study findings indicated that, whilst there are multiple factors of importance in policy implementation across all Consolidated Framework for Implementation Research domains, some factors, such as establishment of roles and responsibilities for implementation and organisational lines of accountability, are feasible for consideration at a hospital level only. In addition, four factors did not reach consensus in terms of feasibility, indicating that it may not be practical to consider all factors of importance when implementing policy; this has important implications for implementation planning and resource allocation.